Comparative Effect of Cucurbita Maxima Seedwith Immunomodulators on Biochemical Parametersin Rabbits - V. Ranganathan, S. Selvasubramanian (Journal of Applied Pharmaceutical Science)
Cucurbita maxima seed was tested for its immuno modulatory effects by comparing it with a proprietary immuno stimulant levamisole HCL using dexamethasone induced immuno suppression model in rabbits in terms of assessing biochemical parameters. Total protein, globulin were found to be higher in Cucurbita maxima treated groups when given alone and with dexamethasone and its response was higher than levamisole in immuno suppressed animals. The study suggests that Cucurbita maxima possesses potential to act as an immuno modulator.
Keywords: Cucurbita maxima,Levamisole Hcl,Dexamethasone,Rabbits